Uma abordagem retórica do gênero debate em sala de aula - Soares, Luciano Bertulino (2017)
This work has for objective to analyze the rhetorical framework for participatory genre debate in the classroom, focusing on argumentative triad formed by ethos, pathos and logos. It is possible to believe that this triad indicate the set of representations between interactors (speaker and auditorium) and is in the service of their speech. For Debate in the classroom, the practice of language in which participants act not only to persuade/convince each other as well as to trade and build knowledge collectively. By Speech Genre, means the whole practice, whether written or oral, in which the subject to act socially; by Rhetoric, by reference to argument which seeks to persuade/convince, as the layout of the Auditorium. Among the authors studied for this research, can be highlighted: a) on the rhetorical devices, Reboul (2004), Perelman and Obrechts-Tyteca (2014) and Fiorin (2015); b) as genre aspects discursive, Marcuschi (2008) and Dolz and Schneuwly (2004). The methodology used in this research has qualitative aspect, in so far as the activity of debate was observed procedurally and the data were interpreted on the basis of its report. Procedural observations understood the universe of six debates, transcripts based on conversational studies, according to Dionysius (2012). From this universe, it was randomly selected a sample of 25% for analysis. Through the analysis, it was possible to observe, first, that the momentum of exchange of genre debate provided the argumentative expressions of ethe disputed ideas and arguments and, secondly, that this combative relationship between different ethe could be resolved thanks to the array of arguments in the genre Debate. In a third moment, stood out the rhetorical role of moderator/mediator as instigator of discussion. Finally, you can consider that the rhetorical framework for participatory genre-classroom Debate comprises not only etheof the debaters, but also the ethos of the moderator/mediator.